Evaluation of water quality pollution indices for heavy metal contamination monitoring: A case study from Curtin Lake, Miri City, East Malaysia - Prasanna, Mohan; Praveena, S.; Chidambaram, S.; Nagarajan, Ramasamy; Aruchunan, Elayaraja (Springer, 2012)
An integrated approach of pollution evaluation indices and statistical techniques was employed to assess the intensity and sources of pollution in Curtin Lake water, Miri City, East Malaysia. Fe, Pb and Se concentrations in most of the water samples exceed the maximum admissible concentration. The heavy metal evaluation index (HEI) shows strong correlations with heavy metal pollution index (HPI) and degree of contamination (Cd), and gives a better assessment of pollution levels. Samples from all the 25 locations in the lake were classified as high in Cd and low in HPI compared with the respective critical values. The modified schemes of HPI and Cd show comparable results with HEI and indicate that about 48 % of the samples with values lower than mean were classed as low contamination and the remaining samples (52 %) with values greater than the mean were classed as medium contamination. Cluster analysis, principal component analysis and pollution indices reveal that the quality of water is mainly controlled by natural/geogenic processes with minor anthropogenic input. US Salinity Laboratory plot and EC classification were also been used to assess the suitability of lake water for agricultural purpose. The current distribution level ofheavy metal in the lake water is of environmental and health concerns and needs attention.